Pengaruh Teknologi, Manajemen Waktu, Pemberian Insentif Dan Sarana Prasarana Kantor Terhadap Produktivitas Kerja Karyawan Di Wilayah Jakarta Timur - Amanda Anasty; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2025)
This study aims to analyze the influence of the role of technology, time management, providing incentives, and infrastructure on employee work productivity in the East Jakarta area. The data collection of this study was carried out by random sampling distributing questionnaires using the Likert scale with values from one to five choices, namely Strongly Disagree = 1, Disagree = 2, Neutral = 3, Agree = 4, and Strongly Agree = 5. 100 respondents who had criteria as employees in East Jakarta were obtained from the distribution of questionnaires. The data in this study was analyzed using a Partial Least Square (PLS)-based Equation Structural (SEM) Model with SmartPLS 4.0 software. Outer Model with calculations of Convergent Validity, Discriminant Validity, Composite Validity, Cronbach's Alpha and Inner Model with calculations of statistical T, R-Square, F-Square, and VIF. The results showed that technology has a significant positive influence on employee work productivity. In addition, time management has a positive but not significant effect on employee work productivity. The provision of incentives has a significant effect on increasing employee work productivity. And infrastructure also has a positive and significant effect on employee work productivity. These results provide useful insights for companies in understanding the factors that affect employee productivity.